PERANCANGAN INTERIOR PERPUSTAKAAN ANAK KEMENDIKBUD DI JAKARTA - Shofiyyah, Nuur; Pujayanto, Dodi (Anggada : Jurnal Desain dan Seni, 2021)
At this time needed a place of infrastructure that can support and assist children in instilling habits in reading, therefore children’s reading library has an important role here to be able to help in meeting the needs needed ranging from providing an interesting atmosphere in the room to the provision of facilities -facilities of children ranging from preschool or early age, namely ages 3 to 6 years to students ranging in age from 7 to 12 years, both in collection facilities, play facilities while learning for children 3-6 years, and indoor facilities. Given the nature of children who are cheerful, excited, and happy to play, it is also necessary to adjust the style of the child’s library space in accordance with the child’s characteristics without eliminating or forgetting the true value of the library’s rules of calm. Therefore, the purpose of this design is how to design a children’s library space with two different groups of children with different needs, habits, development and characteristics, using the coastal concept which has two sides, namely calming and also spirit, passion . The research method used is qualitative research, with a case study approach. The results showed that the children’s facilities and space design in the children’s reading library of the Ministry of Education and Culture of the Republic of Indonesia were still lacking in providing facilities and providing an atmosphere in a suitable room for children who were still happy to play, so the room felt quite boring for children.